Calcium signals in guard cells enhance the efficiency by which abscisic acid triggers stomatal closure - Huang, Shouguang; Waadt, Rainer (The new phytologist, 2019)
During drought, abscisic acid (ABA) induces closure of stomata via a signaling pathway that involves the calcium (Ca2+)-independent protein kinase OST1, as well as Ca2+-dependent protein kinases. However, the interconnection between OST1 and Ca2+ signaling in ABA-induced stomatal closure has not been fully resolved. ABA-induced Ca2+ signals were monitored in intact Arabidopsis leaves, which express the ratiometric Ca2+ reporter R-GECO1-mTurquoise and the Ca2+-dependent activation of S-type anion channels was recorded with intracellular double-barreled microelectrodes. ABA triggered Ca2+ signals that occurred during the initiation period, as well as in the acceleration phase of stomatal closure. However, a subset of stomata closed in the absence of Ca2+ signals. On average, stomata closed faster if Ca2+ signals were elicited during the ABA response. Loss of OST1 prevented ABA-induced stomatal closure and repressed Ca2+ signals, whereas elevation of the cytosolic Ca2+ concentration caused a rapid activation of SLAC1 and SLAH3 anion channels. Our data show that the majority of Ca2+ signals are evoked during the acceleration phase of stomatal closure, which is initiated by OST1. These Ca2+ signals are likely to activate Ca2+-dependent protein kinases, which enhance the activity of S-type anion channels and boost stomatal closure.
Gesehen am 04.11.2019